Development Of Problem Based Learning Modules In Civil Service Subjects - Dwinta Putry, Lyesel; Puspasari, Durinda (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2025)
This study aims to develop a ProblemBased Learning module for the Civil Service subject at SMK Krian 2 Sidoarjo. The background of this study is based on the lack of learning modules that are in line with the curriculum, resulting in a teacher-centered learning process and students having difficulty understanding the material. The research used a research and development method with the ADDIE model, which includes the stages of analysis, design, development, and implementation. The limited test subjects were 20 students in class XI MPLB 2. The research instruments were expert validation sheets for material, language, graphics, and student response questionnaires. The validation results showed that the scores from subject matter experts I and II were 93%, language experts 93%, and graphic experts 95%, which were categorized as very strong. Student responses also showed a percentage of 97.1%, which was categorized as very good. Based on these findings, the PBL-based learning module was declared highly suitable for use, as it was able to help students understand the material, increase motivation, and train critical thinking and problem-solving skills in line with the needs of the world of work.